Narcotic Drugs 2018 - International Narcotics Control Board (United Nations, 2019)
This publication contains information about the licit movement of the internationally controlled narcotic drugs included in the Schedules of the 1961 Single Convention on Narcotic Drugs. This includes information on cultivation of opiate raw materials, on extraction of alkaloids from opium, poppy straw and concentrate of poppy straw; on the manufacture of consumption, utilization, and stocks of opiates and opioids; and international global trade in narcotic drugs as well as in individual countries/territories. The publication also contains the estimated requirements of narcotic drugs for each country and territory.